OPTIMATION OF DECY-13 CYCLOTRON MAGNET MAPPING SYSTEM - Taufik Taufik; Kurnia Wibowo; Frida Iswining Dyah; Suprapto Suprapto (GANENDRA Majalah IPTEK Nuklir, 2016)
OPTIMATION OF DECY-13 CYCLOTRON MAGNET MAPPING SYSTEM. A cyclotron magnet serves to deflect the particle beam so that the beam trajectory is circular and also serves to focus the beam. The magnetic flux density of a cyclotron magnet must satisfy the isochronous field. The magnetic field distribution need to be measured in order to know that the magnetic flux density have fulfilled the isochronous field, therefore a mapping system is needed to obtain the magnetic field distribution data. The design and construction of mechanical system of magnetic field mapping has been carried out in 2013 using fly mode algorithm, but the test results is not accurate yet. Therefore it is necessary to  optimize of the magnetic field mapping system.  The aim of this optimation is to improve the accuracy of step position and the precission of magnetic field measurement of the mapping system of DECY-13 cyclotron magnet.  The research was done by changing the mapping methods that previously based on the fly mode with the step mode. In the step mode, the magnetic field data will be taken when the probe has been completely stopped at the specified position. The magnet mapping system has been optimized with 99.89% of the average step position accuracion.  The mapping system has to start at minimum of 2 hours after the MPS is turned on, in order to get 3.53 gauss of the precision of magnetic field measurement. Although the magnetic field measurement of 1st sensor and 2nd sensor have 6.3 gauss of measurement maximum different but the two sensors have the same pattern of magnetic field average. The mapping result from one of 2 sensors can be used to calculate magnetic field parameter if the magnetic field is symmetric.